Atributos físicos e fisiológicos de sementes de aveia preta - Carbonera, Roberto (2016)
Forage crops practice an important role in animal production in southern Brazil. Among the species, oat stands out due to its higher crop area in winter, occupying an area of 3.8 million hectares in the state of Rio Grande do Sul. For their proper planting and establishment, seeds are produced which must contain high standards of quality, which is measured by analytical laboratories. Given this, the present study aimed to evaluate the physical and physiological attributes of oat seeds, associating quality seeds to the production profile and the possible effects caused by meteorological factors. Was also designed to identify the variables that correlate with the percentage of pure seed and seedling emergence, identify the presence of multicollinearity, the most important variables in relation to the main dependent variable, percentage of normal seedlings, and group the samples for their degrees of similarity. 2,910 samples were assessed, 2,229 seed analysis derived from the seed production process, 357 analyzes for own use of seeds and 324 analyzes tetrazolium analyzed by the laboratory of the UNIJUÍ Agronomy Course seeds, following the methodology described in the rules seed analysis. The results were submitted to analysis of descriptive statistics, the dispersion of the data, the Pearson linear correlation coefficients were estimated, the diagnosis of multicollinearity, the direct and indirect effects through path analysis and grouping between samples. The seeds produced according to the national seed and seedling system showed excellent levels of physical and physiological quality in the years 2006 to 2010. Between 2011- 2014, 14 and 14.5% of the seeds have been compromised by the presence of other seed species cultivated and tolerated harmful, respectively. The proper use of seeds showed wide variability with 18.1 and 31.7% of samples below the standard for germination in the years 2006 to 2010 and 2011-2014, respectively, while the samples analyzed by the tetrazolium test showed disapproval levels 19.4 and 12.5%, respectively. It is noteworthy that the seed quality is related to the years with levels of rainfall and temperatures appropriate to the vegetative development, physiological maturity and harvest. The variable normal seedlings showed the highest correlation, a negative sign with dead seeds. Abnormal seedlings variables and dead seeds showed the highest direct effects on germination percentage, negative sign and cluster analysis revealed the existence of three similarity groups of seeds produced according to the national system of seed plants and four groups in seed own use.